Survey on Major Blackouts Analysis and Prevention Methodologies - Chakraborty, N.C; Banerji, A; Biswas, S.K (Michael Faraday IET International Summit 2015, 2015)
Power blackouts are major catastrophic failures in large inter connected power systems. Risk of blackouts is more than expected and must be considered in the power system studies. In past, many power blackouts occurredworldwide. An attempt has been made to summarize those major blackouts with their effects. To resolve the risk factors identified by the researchers various methodologies were proposed. This paper surveys major blackouts, analyze the reasons behind them and report major prevention methodologies proposed by various authors and aim at providing a broad perspective on blackouts in power system to researchers and application engineers. Classified manner in which the references are presented will serve them as quick and useful reference.